A new two-round certificateless authenticated key agreement protocol without bilinear pairings - He, Debiao; Chen, Yitao; Chen, Jianhua; Zhang, Rui; Han, Weiwei (Mathematical and computer modelling, 2011)
Certificateless public key cryptography (CLPKC), which can simplify the complex certificate management in the traditional public key cryptography and resolve the key escrow problem in identity-based cryptography, has been widely studied. As an important part of CLPKC, certificateless two-party authenticated key agreement (CTAKA) protocols have also received considerable attention. Recently, many CTAKA protocols using bilinear pairings have been proposed. But the relative computation cost of the pairing is approximately twenty times higher than that of the scalar multiplication over elliptic curve group. To improve the performance, several CTAKA protocols without pairings have been proposed. In this paper, we will show a latest CTAKA protocol is not secure against a type 1 adversary. To improve the security and performance, we also propose a new CTAKA protocol without pairing. At last, we show the proposed protocol is secure under the random oracle model.